Rate of infection (tuberculosis) in brazilians IBD private patients: follow-up 15 years - Cury, Didia Bismara (2024)
Background – Latent tuberculosis (LTB) is a condition where the patient is infected with Mycobacterium tuberculosis but does not develop active TB. There’s a possibility of tuberculosis (TB) activation following the introduction of anti-TNFs. Objective – To assess the risk of biological therapy inducing LTB during inflammatory bowel diseases (IBD) treatment over 15 years in a high-risk area in Brazil. Methods – A retrospective study of an IBD patients’ database was carried out in a private reference clinic in Brazil. All patients underwent TST testing and chest X-ray prior to treatment, and once a year after starting it. Patients were classified according to the Montreal stratification and risk factors were considered for developing TB. Results – Among the analyzed factors, age and gender were risk factors for LTB. DC (B2 and P) and UC (E2) patients showed a higher number of LTB cases with statistical significance, what was also observed for adalimumab and infliximab users, compared to other medications, and time of exposure to them favored it significantly. Other factors such as enclosed working environ-ment have been reported as risk. Conclusion – The risk of biological therapy causing LTB is real, so patients with IBD should be continually monitored. This study reveals that the longer the exposure to anti-TNFs, the greater the risk.